Pembentukan Karakter Religius Siswa Melalui Kegiatan Ekstrakurikuler Keagamaan di Sd Islam Plus Darus Salaam Pondok Jaya - Sarah, Raike; Suharsongko, M.Edi; Rahmawati , Sri (Journal of Comprehensive Science, 2025)
This study aims to explore the formation of students’ religious character through religious extracurricular activities at SD Islam Plus Darus Salaam Pondok Jaya. The background of this research is based on the importance of character education in schools, particularly religious character as a fundamental aspect in shaping morally upright students. This research employs a qualitative approach with a case study method. Data were collected through observation, interviews with the principal, teachers, and students, as well as documentation of activities. The results indicate that the development of students' religious character is carried out through the synergy between daily religious routines and extracurricular activities. Activities such as congregational Dhuha prayer, group prayers, Qur’an reading and writing (BTQ), Qur’an recitation improvement (Tahsin), and the commemoration of Islamic holidays serve as effective means of instilling Islamic values in students. Furthermore, the success of this program is supported by the principal's commitment, active teacher involvement, and adequate facilities and infrastructure. Although challenges such as students’ lack of awareness and diverse family backgrounds exist, the school continuously promotes routine practice, provides guidance, and fosters cooperation with parents to address these issues. In conclusion, religious extracurricular activities at SD Islam Plus Darus Salaam play a significant role in shaping students’ religious character in a systematic and sustainable manner.